-2(-8x+4)-8x=2(x-4)-2

Simple and best practice solution for -2(-8x+4)-8x=2(x-4)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(-8x+4)-8x=2(x-4)-2 equation:


Simplifying
-2(-8x + 4) + -8x = 2(x + -4) + -2

Reorder the terms:
-2(4 + -8x) + -8x = 2(x + -4) + -2
(4 * -2 + -8x * -2) + -8x = 2(x + -4) + -2
(-8 + 16x) + -8x = 2(x + -4) + -2

Combine like terms: 16x + -8x = 8x
-8 + 8x = 2(x + -4) + -2

Reorder the terms:
-8 + 8x = 2(-4 + x) + -2
-8 + 8x = (-4 * 2 + x * 2) + -2
-8 + 8x = (-8 + 2x) + -2

Reorder the terms:
-8 + 8x = -8 + -2 + 2x

Combine like terms: -8 + -2 = -10
-8 + 8x = -10 + 2x

Solving
-8 + 8x = -10 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-8 + 8x + -2x = -10 + 2x + -2x

Combine like terms: 8x + -2x = 6x
-8 + 6x = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
-8 + 6x = -10 + 0
-8 + 6x = -10

Add '8' to each side of the equation.
-8 + 8 + 6x = -10 + 8

Combine like terms: -8 + 8 = 0
0 + 6x = -10 + 8
6x = -10 + 8

Combine like terms: -10 + 8 = -2
6x = -2

Divide each side by '6'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| (1/2)2x=32 | | 67.50=2.50x+20 | | Y^2-6y+c=1 | | -2w+16=-5(w-5) | | -3(1-y)+2=2(x-4) | | -9-x=-3x+3 | | x+8/3=-14 | | W/4=2.1 | | 4=2(y+4)-4y | | 67.5=2.50x+20 | | x-2y+-3=0 | | -30p=30 | | (2p-10)(150)=4500-100p | | 2x-6=-3x+14 | | 14+3x(x+10)=7(2x+4) | | 3z+5=-1 | | 2x+1+4x-4+3x+1=34 | | 2x+1+4x-4+3x+1=180 | | -7+x=-3x+5 | | (2x^4y)(3x^5y^8)= | | r-47=41 | | -11+3x=5-x | | 3x-7(-2x-13)=3(-2x+9) | | 500+2x=10000-4x | | -1/4=2/3x-2/5 | | 1/4=4 | | 6t+5=t+25 | | 15x=2/3 | | -14=2x | | 3x-20=15-2x | | 3+5x-4-7x=-4x+1 | | 3b^20/3a^14 |

Equations solver categories